2004
DOI: 10.1111/j.1365-2265.2004.02108.x
|View full text |Cite
|
Sign up to set email alerts
|

Type V phosphodiesterase inhibitor treatments for erectile dysfunction increase testosterone levels

Abstract: OBJECTIVE Lack of sexual activity due to erectile dysfunction (ED) decreases testosterone (T) levels through a central effect on the hypothalamic-pituitary axis.In this paper we studied the effect of different type V phosphodiesterase (PDE5) inhibitor treatments for ED on the reversibility of this endocrine pattern. DESIGN Open-label, retrospective study. PATIENTS Seventy-four consecutive patients were treated on demand with sildenafil (Sild) (50 mg) and tadalafil (Tad) 20 mg. MEASUREMENTS The success in sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 34 publications
5
65
0
Order By: Relevance
“…This finding was also reported by Carosa and coworkers 21,22 in 74 patients with ED receiving sildenafil and tadalafil. They explained this finding by the fact that lack of sexual activity due to ED decreases testosterone levels through a central effect on the hypothalamic-pituitary axis.…”
Section: Discussionsupporting
confidence: 75%
“…This finding was also reported by Carosa and coworkers 21,22 in 74 patients with ED receiving sildenafil and tadalafil. They explained this finding by the fact that lack of sexual activity due to ED decreases testosterone levels through a central effect on the hypothalamic-pituitary axis.…”
Section: Discussionsupporting
confidence: 75%
“…Several observational trials suggested an improvement of total testosterone serum levels in men with erectile dysfunction after 3 months of various therapies (29,30). These authors suggested that the improvement of testosterone levels was a consequence of improved sexual activity in men using impotence drugs (29,30). In this way, testosterone deficiency was interpreted both as the cause and the effect of impotence (30).…”
Section: Discussionmentioning
confidence: 99%
“…We show that PDE5i can improve testosterone production in hypogonadal men, although the mechanism remains unclear. Several observational trials suggested an improvement of total testosterone serum levels in men with erectile dysfunction after 3 months of various therapies (29,30). These authors suggested that the improvement of testosterone levels was a consequence of improved sexual activity in men using impotence drugs (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that testosterone influences both the level of eNOS protein and erectile functionality. 29 Moreover, Carosa et al 30 have reported increased testosterone plasma levels after sildenafil citrate treatment. In this study, no changes in free testosterone plasma levels were observed after sildenafil treatment, which diminished the involvement of testosterone in the findings reported here.…”
Section: Sildenafil Citrate and Mononuclear Cells J García-cardoso Et Almentioning
confidence: 99%